Addressing English Language Anxiety in High School Students - Vivit Rosmayanti (CV. Eureka Murakabi Abadi, 2024)
This research study aims to examine the factors that trigger anxiety among students learning the English language in the classroom within a private senior high school setting in Makassar, Indonesia. A qualitative approach was employed whereby data were obtained through semi-structured interviews, classroom observations, and the Foreign Language Classroom Anxiety Scale (FLCAS). A total of 20 students came on board, representing a selection of students at various levels of proficiency. The study outlines learners’ anxiety based on their personal, environmental, and instructional factors. Some of the personal reasons that anxiety is created include fear of negative judgments, low self-esteem, or even previous harsh remarks about an individual; such factors do decrease students’ involvement in the lessons. Some other more global aspects, such as a worry about what others think and competitive environments, aggravated the anxiety felt by the students. So, contradictory to this explanatory factor, a range of focal elements, including how difficult the task was, whether there was a focus on speaking accurately, and the nature of tests targeting particular tasks, also proved to create a high level of anxiety. The FLCAS questionnaire revealed that students did experience quite a bit of test anxiety and also apprehensiveness of test taking. In classroom settings, the researchers were able to notice some behavioral aspects of anxiety, such as the inability to engage verbally and the lack of willingness to maintain eye contact during conversations. The study recommends that instead of making language learning full of competition, instructors should try to find good explanations of the language and assist them in overcoming that language anxiety. Besides, there is a need for an in-depth study of the ways that may help to decrease anxiety in English language classrooms.